African Economic Renaissance: A Case Study of Rwanda and Angola. Issue 2 (July 2018) - Jauhari, Alka
In the past century, Africa has been visibly absent from the world's growth map. At the dawn of the twenty-first century, however, many countries in Africa have guided their way into achieving impressive economic growth. The International Monetary Fund (IMF) identified six countries from Africa—Rwanda, Mozambique, Nigeria, Angola, Chad and Ethiopia—in the top ten fastest growing economies of the world during 2001–10. Among these countries, some are resource-rich while others are non-resource-based economies. Both have however achieved growth through the adoption of targeted economic policies. With an examination of the post-conflict reconstruction of Rwanda (non-resource) and Angola (resource-rich), the article analyses the policies adopted and measures undertaken by the two for achieving economic growth as well as the prospects for sustainability of their growth.